COMUNICAÇÃO DA EQUIPE DE ENFERMAGEM COM DEFICIENTE AUDITIVO COM SURDEZ SEVERA: UM ESTUDO EXPLORATÓRIO - Maria Márcia Bachion; Maria Alves Barbosa; Carmelita Gomes Rosa (Universidade Federal de Goias, 2000)
This exploratory study has the finality to identify related aspects to the nursing staff with the auditive handicapped patient with severe deafness. The subjects were 31 members of the nursing staff of the Medical and Surgical Clinics of a University Hospital in the State of Goiás, using a questionary as a data acess tool. The results shows us the resources used by nursing staff to promote the communication with this kind of patient, the difficults that they have and how they deal with these situation. We hope that this paper can serve as a baseline to new research in order to minimize the interaction barrier between the nursing staff and severe deaf patients.